Vpliv zgodnje medicinske rehabilitacije na sposobnost gibanja starostnikov po zlomu proksimalnega dela stegnenice - Bubnjar, Marija (Rehabilitacija (Ljubljana), 2018)
Background: Hip fracture is a common injury in the elderly. We wanted to check the influence of early medical rehabilitation on mobility of such patients, and how much it depends on age, ability to walk and perform daily activities before the fracture, cognitive function, duration of hospital treatment, complications during treatment and social support. Methods: We included 50 injured people who had been hospitalised at the trauma department of the University Medical Centre (UMC) Ljubljana. We evaluated functional capacity with the De Morton Mobility Index (DEMMI) and cognitive function with the Clock drawing test. Other data were obtained from medical records and using a questionnaire. Results: The average progress in DEMMI score was 17.4 points. In the elderly who lived alone the average DEMMI progress was 22.8 points, in those who walked and performed basic everyday activities independently it was 23.2 points and 20.5 points, respectively. In those over 90 years old and with cognitive decline the average DEMMI progress was 5.8 points and 15.4 points, respectively. The success of early medical rehabilitation depended on the duration of hospitalisation: the average DEMMI score increase for every day of hospitalisation was 1.4 points; the effect of complications during the treatment has not been confirmed. Conclusion: Early medical rehabilitation after hip fracture in the elderly at the trauma department of the UMC Ljubljana improved their mobility. Age, cognitive status, daily activities, mobility and place of residence before the injury were associated with the rehabilitation outcome.
Keywords: Aged; De Morton lestvica funkcionalne zmogljivosti; De Morton Mobility Index; DEMMI; early rehabilitation; elderly; hip fracture; Hip Fractures; mobility; mobilnost; rehabilitation; starostniki; zgodnja rehabilitacija; zlom kolka